Development and Characterization of Carbon Quantum Dots from Green Synthesis Route for Potential Supercapacitor Application - CHANDERENG, NAWIIN (IRC, 2021)
Carbon quantum dots (CQDs) is a simple nanotechnology material which have reached out wide throughout the world especially in electrolysis process especially in forming a supercapacitor.